Teknis Pendampingan Pastoral Konseling Terhadap Anak Yang Berduka Karena Kematian Orang Tua Akibat Covid-19 - Asmat Purba; Alon Mandimpu Nainggolan; Martin L Manao (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article aims to analyze, describe and propose how to technically provide pastoral assistance to children who experience grief due to the death of their parents due to Covid-19. The method used is descriptive qualitative, with a theological approach, Christian counseling, and applicative. Through this study found five consequences of the experience of grief in children, namely: children experience deep grief, trauma, anger, anxiety, and psychophysiological illness. That is why the author proposes four technical pastoral care for grieving children, namely, the counselor conducting interviews, the counselor being a good listener, the counselor guiding the recovery, and building a bereavement healing group. Through this research, it is hoped that ministers of God in various contexts can take part in pastoral care services for children grieving because of their parents’ death due to the viciousness of Covid-19. Children are the next generation of the church, so they must be helped according to their stage of development to be able to get through grief.